Can MTA be: Miracle trioxide aggregate? - Reshma M Naik; Pushpa S Pudakalkatti; Sanjeevini A Hattarki (Wolters Kluwer Medknow Publications, 2014)
Mineral trioxide aggregate (MTA) has been used for more than 10 years in the dental community and has often been thought of as a material of choice for the endodontist. The dental pulp is closely related to periodontal tissues through apical foramina, accessory canals, and dentinal tubules. Due to this interrelationship, pulpal diseases may influence periodontal health and periodontal infections may affect pulpal integrity. It is estimated that pulpal and periodontal problems are responsible for more than 50% of tooth mortality. Thus, these associations recommend an interdisciplinary approach. MTA appears to exhibit significant results even in periodontal procedures as it is the first restorative material that consistently allows for over-growth of cementum and may facilitate periodontal tissue regeneration. Thus, in the present review, an attempt is made to discuss the clinical applications of MTA as an interdisciplinary approach.